2013
DOI: 10.4236/ajps.2013.42047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Variations in Seed Vigour Characters of West African Rice (<i>Oryza sativa</i> L.) Genotypes Using Multivariate Technique

Abstract: Seeds of 24 West African rice (Oryza sativa L.) genotypes were evaluated for seed vigour traits in the laboratory and field in two cropping seasons at the Research Farm of Federal University of Agriculture, Abeokuta, Nigeria. Seed yields of these genotypes were also determined in the field during the two seasons. Data collected on seed vigour traits were subjected to multivariate analysis including principal component analysis (PCA) and cluster analysis. The first three axes of the principal component analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…Since the variation is high (≥25 %) for principal components, this information can be used along with cluster analysis to identify the related genotypes (Ahmad et al 2015 ). Our results are in agreement with Adebisi et al ( 2012 ), who reported that the first three principal components were the most important in reflecting the variation patterns among accessions. The markers associated in classifying the genotypes can be recommended in differentiating population subgroups.…”
Section: Resultssupporting
confidence: 93%
“…Since the variation is high (≥25 %) for principal components, this information can be used along with cluster analysis to identify the related genotypes (Ahmad et al 2015 ). Our results are in agreement with Adebisi et al ( 2012 ), who reported that the first three principal components were the most important in reflecting the variation patterns among accessions. The markers associated in classifying the genotypes can be recommended in differentiating population subgroups.…”
Section: Resultssupporting
confidence: 93%
“…These specific associations among the genotypes present in different clusters can be harnessed to improve a significant trait. These findings are in agreement with previous studies on rice genotypes (Adebisi et al 2013a) and maize inbreds (Adebisi et al 2013b). Good germination and better seedling vigour are very important in case of pearl millet seed production as pearl millet is usually grown in rain-fed environment.…”
Section: Resultssupporting
confidence: 92%
“…In most of the studies, genetic variation among inbred lines or genotypes is being usually assessed by using morphological characters and isozyme markers. There are several studies in literature relating to diversity analysis based on morphological characters (Loumerem et al 2008, Pucher et al 2015, Kumari et al 2016 but the studies related to seed vigour characters are very few (Adebisi et al 2013a, Jan et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological characterization combined with multivariate statistical methods, such as cluster analysis, are useful tools for screening accessions (Akintobi et al 2002;Golparvar 2013;Adebisi et al 2013). Hierarchical cluster analysis separated the java olive populations based on the fruit, seed morphological and biochemical characteristics into three groups, i.e.…”
Section: Population Clusteringmentioning
confidence: 99%